Analysis of full reference quality metrics for image transmission over a MIMO OWC channel under varying turbulent conditions. (3rd January 2023) - Gill, Harpuneet Singh; Singh, Maninder Lal; Singh, Mandeep; Priyanka,; Kaur, Sehajpal; Kaur, Hardeep
Summary: The integrated OWC‐PON architecture has a potential to overcome the limitations of existent RF technology and eliminate the last mile bottleneck in geographically constrained access networks thus providing real sense broadband from core to user. However, phenomenon such as atmospheric turbulence causes performance degradation in such systems. In the dissemination of multimedia services, the performance is the ultimate quality as perceived by end user's visual senses. To ascertain this quality in quantitative terms, full reference quality metrics are employed for communication purposes. This paper deals with classification, evaluation and analysis of various image quality assessment metrics for image transmission over OWC channel under varying turbulent conditions. The performance enhancement in terms of these metrics is investigated by deploying MIMO diversity reception. Moreover, a prediction model for SSIM is developed and compared for both SISO and MIMO links. The results show an improvement in IQA metrics with diversity reception. SSIM can be predicted in terms of log of refractive index structure parameter by a fourth order polynomial model for both SISO and MIMO receptions under all regimes of turbulence. The goodness of the fit statistics is presented along with the models to provide for their accuracy and reliability. Abstract : In the dissemination of multimedia services, the performance is the ultimate quality as perceived by end user's visual senses. To ascertain this quality in quantitative terms, full reference quality metrics are employed for communication purposes. This paper deals with classification, evaluation and analysis of various image quality assessment metrics for image transmission over OWC channel under varying turbulent conditions. The performance enhancement in terms of these metrics is investigated by deploying MIMO diversity reception.